Downshifting: Stratification Effects - Евгения Владимировна Лисова (Journal of Economic Sociology, 2010)
The paper deals with the phenomenon of downshifting – the sharp and voluntary downward change of social status, refuse from conventional  goods and prestige in order to have personal comfort lifestyle. The author tried to build in this phenomenon into the current classifications and describe the downshifters as a group on the basis of the stratification criteria.